Identification of School’s Roles, Adolescent Access, and Exposure to Information on Adolescent Reproductive Health - Nafisah, Lu'lu; Rizqi, Yuditha Nindya Kartika; Aryani, Aisyah Apriliciciliana (Poltekkes Kemenkes Tanjung Karang, 2023)
The problems experienced by adolescents have an impact on their growth and development and their future. One of the main factors behind this problem is the exposure to information about adolescent reproductive health. This study aims to describe adolescent exposure to information on reproductive health. This type of research is observational with a cross-sectional study design. The sample in this study was 169 unmarried high school students aged 15–20 years who live in Banyumas Regency, totaling 169 people. Most adolescents are female (78.7%), 17 years old (40.8%), and 16 years old (37.9%), live with their parents (95.9%), use social media to find information about adolescent reproductive health (67.5%), considered parents as a more trusted source of information (27.8%) and social media as a less trusted source of information (50.9%). Most adolescents have received counseling about adolescent reproductive health at school (84.6%), provided Youth Information Center and Counseling Program in their schools (36.1%), and never received information about Generation Planner (68%) and Youth Information Center and Counseling Program (58.6%). Adolescents have sufficient access to information on adolescent reproductive health. Still, not a few adolescents have not received information about programs related to Generation Planner and Youth Information Center and Counseling Program. Schools already provide information on adolescent reproductive health and sexuality. However, only a few adolescents receive information about family planning and contraception and are aware of a school's youth counseling and information center.